Innovative technology for the production of macaroni products made of emmer wheat flour - Khmeleva E. (EDP Sciences, 2021)
Macaroni products as a product of mass consumption can serve as an object for enriching the human body with useful components by using non-traditional raw materials. The authors propose an innovative technology for the production of macaroni products made of a mixture of wheat and emmer wheat flour with the addition of wheat bran as a source of dietary fibers, which makes it possible to give functionality to the products and at the same time improve their quality.